CARTOGRAPHY AND GIS EDUCATION IN GEOMATIC ENGINEERING - Basaraner, M.; Ulugtekin, N.; Dogru, A. Ozgur (BULGARIAN CARTOGRAPHIC ASSOC, 2014)
Cartography and GIS education is largely undertaken by geomatic engineering (a.k.a. geodesy and geoinformatics, geospatial science or surveying and mapping/geoinformation) and geography departments of universities as part of their undergraduate and graduate programmes. Individual bachelor programmes on cartography are very few and in trend of decreasing while individual GIS or geoinformatics undergraduate programmes including some cartographic courses have been emerging. On the other hand, individual graduate programmes are increasing on these subjects apart from specialisations within geomatic engineering or geography programmes. The aim of this study is to examine different international higher education models of geomatic engineering with focus on cartography and GIS and show similarities and differences as well as make some proposals for possible curricula on cartography and GIS. As a result, the findings of this study may help improve the current curricula on cartography and GIS in geomatic engineering related departments.
Keywords: Geography